Research on The Influence of Internet Subculture on The Values of Young College Students - Guo, Shuang (Transactions on Social Science, Education and Humanities Research, 2024)
Internet subculture has novel forms and diverse contents, providing college students with a free space to vent their emotions, release stress, and seek recognition. It has a strong appeal to young college students and affects the formation and change of college students' values. In terms of the formation of college students' beliefs and its impact on faith education, Internet subculture has a dual aspect. It not only has a positive role in promoting the transformation of faith education in communication methods and promoting the advancement of communication content with the times, but it can also produce deconstruction and resistance to the orientation of mainstream faith values. Negative effect. In-depth disclosure of the impact of Internet subculture on college students' faith education, and then proposing corresponding countermeasures, has become an important topic in deepening and innovating the research on college students' faith education in the Internet era. We should change our thinking, change the problem perspective into the advantage perspective, and look at Internet subculture and its impact rationally. Starting from the four aspects of society, cyberspace, universities and college students themselves, we should build an educational synergy to lead the healthy development of Internet subculture, standardize its communication platform, give full play to the positive impact of Internet subculture, and weaken its negative impact. In order to deal with Internet sub-culture provide targeted countermeasures to influence the values of college students.